К фауне саркофагид (Diptera. Sarcophagidae) СССР. I. Триба Sarcophagini (Sarcophaginae) (по материалам коллекции Института зоологии АН УССР) - Вервес, Ю.Г. (Вестник зоологии, 1974)
The results of processing the collection funds at the Institute of Zoology of the Ukrainian Academy of Sciences are considered. 95 species of sarcophagides are found, among them Sarcophaga zumptiana Lehrer —a new species for the USSR fauna. The data on distribution of 62 species of the Sarcophagini tribe from the Sarcophaginae subfamily are presented.